Reflection on care-taking from hemodialysis: the body as a mediator of the relation between the one who takes care and the one that is well-taken care of - Fernandes Costa Lima, Antônio (O Mundo da Saúde, 2006)
This study has as its purpose a theoretical reflection on the conception of the body in the interaction between the health professional and the chronic renal patient from the scene of hemodialysis. It aims to present a critical discussion on the formation of the health professional, focused in the corporal processes, standing out the importance of rescuing human beings mental and spiritual dimension.